ADENIUM BOEHMIANUM” DALAM PERANCANGAN KURSI TAMAN - Reza Mahardika Kusuma; Jati Widagdo (SULUH: Jurnal Seni Desain Budaya, 2020)
The increasing number of houses that have gardens andthe need for relaxation in the garden, of course, is anopportunity for innovative seating needs but does not neglectthe beauty and comfort of the user. In the furniture sector, thereis a demand to be able to adapt to conditions and conditions atevery level as well as the development of the productionprocess, with the demands of the community's needs not onlyfor taste, but also with the beauty of furniture, as well as tryingto meet functional demands. Wajip furniture products aretailored to the wearer and where the product is placed. Tableproducts and garden chairs with the idea of "Adeniumboehmianum", because flowers also have a close relationshipwith the garden, the concept of "Adenium boehmianum" is verysuitable to be applied to products for garden tables and chairs.The research method used is descriptive qualitative with datacollection techniques used are observation, documentation, andinterviews. In the design of tables and chairs, "Adeniumboehmianum" uses a thematic design process to boldly exploreforms and construction systems.